Nothing to Lose - Child, Lee (London Bantam Press, 2008)
Two small towns in Colorado: Hope and Despair. Between them, nothing but twelve miles of empty road. Jack Reacher can't find a ride, so he walks. All he wants is a cup of coffee. What he gets are four redneck deputies who want to run him out of town. Mistake. They're picking on the wrong guy.
Keywords: Reacher, Jack (Fictitious character) -- Colorado -- Conspiracies